Teachers’ individual characteristics and job satisfaction in Southern Papua - Basilius Redan Werang; Seli Marlina Radja Leba; Sandra Ingried Asaloei (Journal of Education and Learning (EduLearn), 2022)
This study aimed to examine the possible impact of individual characteristics of teachers on their job satisfaction in the elementary schools of Southern Papua, Indonesia. To do so, two survey questionnaires were distributed to 319 respondents. Employing the SPSS software version 21, obtained data were statistically analyzed using simple linear regression. Result of the data analysis revealed a significant positive impact of the individual characteristics of teachers on their job satisfaction in the elementary schools of Southern Papua. This study provides knowledge on how the individual characteristics of elementary school teachers affect their job satisfaction within the real context of Southern Papua. Therefore, finding of this study may supposedly contribute the body of knowledge by providing the valuable extension of relevant studies in other parts of Indonesia as well as in other countries.